Diabetes: Recent Advances and Future Perspectives - Miodrag Janić; Andrej Janež; Mohamed El-Tanani; Viviana Maggio; Manfredi Rizzo (Biomedicines)
Diabetes is a chronic metabolic disorder distinguished by persistent hyperglycemia [...]